2017
DOI: 10.3390/su9060902
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Naturally Ventilated Office Spaces Not Popular in New Zealand?

Abstract: Abstract:In this paper, we investigated the reason(s) why natural ventilation is not as popular as air-conditioned or mixed-mode ventilation systems in Green-rated office buildings in New Zealand. To achieve this, we had three objectives. Firstly, we reviewed the Green Star criteria for thermal comfort in office buildings to ascertain which ventilation system the NZ Green Star rating tool promotes. Secondly, we ascertained the perception of occupants in office buildings regarding thermal comfort. This was foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…Based on the findings of Rasheed et al, (2017) that occupants have less sick leaves in naturally ventilated office spaces, the study reported in this paper is a step towards exploring the possibility of achieving environmental sustainability without sacrificing occupants' comfort in naturally ventilated buildings. It aims at identifying perceived comfort differences across a range of variables such as lighting, noise and temperature between naturally ventilation and mixed-mode ventilation systems.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the findings of Rasheed et al, (2017) that occupants have less sick leaves in naturally ventilated office spaces, the study reported in this paper is a step towards exploring the possibility of achieving environmental sustainability without sacrificing occupants' comfort in naturally ventilated buildings. It aims at identifying perceived comfort differences across a range of variables such as lighting, noise and temperature between naturally ventilation and mixed-mode ventilation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed-mode buildings have been reported to provide better environmental comfort and occupant satisfaction than naturally ventilated buildings (Brager & Baker, 2009;Alessi et al, 2014, Rasheed et al, 2017. The basic benefit of mixed-mode ventilation over natural ventilation is the maintenance a satisfactory indoor environment by alternating between and combining natural and mechanical systems (air-conditioners) to avoid the cost, energy penalty and consequential environmental effects of full year-round air conditioning (Brager, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations